A Comparison of Historical Control Data From Cynomolgus Macaques (Macaca Fascicularis) of Chinese, Cambodian, and Vietnamese Origin. (July 2022) - Liepnieks, Molly; Carter, Caitlyn; Caruso, Michael J.; Lloyd, Zac; Muzyka, Michael; Patrick, Daniel
Cynomolgus macaques, the most commonly utilized nonhuman primate in nonclinical toxicology studies, are acquired from purpose-bred colonies across various geographic locations, including China, Cambodia, and Vietnam. Importation challenges and limited availability have restricted animals suitable for inclusion in nonclinical studies. The coronavirus disease 2019 (COVID-19) outbreak further stressed supply chains, reducing the ability to source animals from a singular location to complete a drug development program. These challenges raised concerns of increased variability in study endpoints due to heterogeneity of animals and that this could subsequently impact historical control data and toxicology study interpretation. To investigate the impact of Chinese, Vietnamese, or Cambodian geographic origin on standard nonclinical toxicology study endpoints, historical control data from studies conducted at a single facility from 2005 to 2020 were compiled and evaluated for the following: clinical observations, body weight, ophthalmoscopic examinations, and clinical and anatomic pathology data. Study populations consisted of 2- to 5-year-old cynomolgus macaques sourced from China ( n = 750 males/741 females), Cambodia ( n = 282 males/271 females), and Vietnam ( n = 122 males/120 females). Interpretation of the various data demonstrated no notable differences in standard toxicology study endpoints or background findings among cynomolgus macaques originating from China, Cambodia, or Vietnam.